S₁-state decay dynamics of benzenediols (catechol, resorcinol, and hydroquinone) and their 1:1 water clusters - Kim, Kuk Ki (2022)
The S1-state decaying rates of the three different benzenediols, catechol, resorcinol, and hydroquinone, and their 1:1 water clusters have been state-specifically measured using the picosecond time-resolved parent ion transients obtained by the pump (excitation) and probe (ionization) scheme. The S1 lifetime of catechol is found to be short, giving τ ∼ 5.9 ps at the zero-point level. This is ascribed to the H-atom detachment from the free OH moiety of the molecule. Consistent with a previous report (J. Phys. Chem. Lett. 2013, 4, 3819-3823), the S1 lifetime gets lengthened with low-frequency vibrational mode excitations, giving τ ∼ 9.0 ps for the 116 cm-1 band. The S1 lifetimes at the additional vibronic modes of catechol are newly measured, showing the nonnegligible mode-dependent fluctuations of the tunneling rate. When catechol is complexed with water, the S1 lifetime is enormously increased to τ ∼ 1.80 ns at the zero-point level while it shows an unusual dip at the intermolecular stretching mode excitation (τ ∼ 1.03 ns at 146 cm-1). Otherwise, it is shortened monotonically with increasing the internal energy, giving τ ∼ 0.67 ns for the 856 cm-1 band. Two different asymmetric or symmetric conformers of resorcinol give the respective S1 lifetimes of 4.5 or 6.3 ns at their zero-point levels according to the estimation from our transients taken within the temporal window of 0-2.7 ns. When resorcinol is 1:1 complexed with H2O, the S1 decaying rate is slightly accelerated for both conformers. The S1 lifetimes of trans and cis forms of hydroquinone are measured to be more or less same, giving τ ∼ 2.8 ns at the zero-point level. When H2O is complexed with hydroquinone, the S1 decaying process is facilitated for both conformers, slightly more efficiently for the cis conformer.